Three Simple Spectrophotmetric Methods Using for Estimation of Vancomycin in Pure and Vial Injection - Abdullwahid Jasim, Ala'a (Al-Nahrain Journal of Science, 2020)
Three rapid, accurate and ecological friendly spectrophotometric methods are used for determination of  Vancomycin at wavelength 200 nm for the  zero-order method, 195-205 nm for the area under the curve (AUC) method and 200 nm for  the first derivative method(D1). A calibration graph shows that  Beer's law is obeyed over the concentration range between  4-16 mg.L-1 for all three methods with a correlation coefficient of 0.994, 0.998 and  0.997 for zero-order, AUC and  D1 at valley 200 nm, respectively. Average of  Rec.% were found to be of 100.870, 101.425 and  99.515 for zero-order, AUC and  D1 at valley 200 nm, respectively. Statistical analysis of data reveals that  all three methods are precise, accurate and suitable for the application Vancomycin in pure and pharmaceutical preparations.